Impact of Ads with Celebrity Endorsements on Learners' intention to buy (International Journal of Food and Nutritional Sciences, 2022)
A celebrity's appearances in a commercial likely affect buyers' purchasing choices. Furthermore, these commercials lift information of the creation, which can direct to augmented procure intent and, eventually, higher vending. One of the marketing strategies businesses use to expand understanding of and garner support for their goods and services is the endorsement of celebrities. This expectation is frequently not met because a terrible reputation for a celebrity endorser and the product they are endorsing can all lead to negative reactions towards the brand rather than either way around. The study indicated that celebrity-endorsed advertising significantly affects students' buying intention. The analysis advises that the various components should be carefully blended to produce celebrity-endorsed and non-celebrity-endorsed advertisements. Similarly, before a celebrity endorses a product, the public's perception of them should be carefully considered to ensure it will not harm the brand.